2022
DOI: 10.1101/2022.11.27.518101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profound impact of hippocampal output on the interpretation of tactile input patterns in SI neurons

Abstract: Due to continuous state variations in neocortical circuits, individual SI neuronsin vivodisplay a variety of intracellular response types to repeated presentations of the exact same tactile input pattern. The specific intracellular response obtained depends on a time-evolving combination of the specific input with the current neocortical state. To manipulate the internal cortical state, we here used brief electrical stimulation of the output region of the hippocampus, which preceded the delivery of specific ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…We have previously reported that the exact same tactile input pattern can trigger a wide variety of responses in individual primary somatosensory (S1) cortical neurons (Norrlid et al, 2021). The response variations are due to internal state variations in the neocortical neuronal network globally, which can be demonstrated by weakly perturbing either a remote area of the cortex (Etemadi et al, 2022;Wahlbom et al, 2019) or the output of the hippocampus (Etemadi et al, 2023). These response variations in individual neurons can be explained as a consequence of subtle changes in the state of the neocortex globally, which in turn can alter the number of "open" network pathways supplying the recorded neuron with tactile information.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the exact same tactile input pattern can trigger a wide variety of responses in individual primary somatosensory (S1) cortical neurons (Norrlid et al, 2021). The response variations are due to internal state variations in the neocortical neuronal network globally, which can be demonstrated by weakly perturbing either a remote area of the cortex (Etemadi et al, 2022;Wahlbom et al, 2019) or the output of the hippocampus (Etemadi et al, 2023). These response variations in individual neurons can be explained as a consequence of subtle changes in the state of the neocortex globally, which in turn can alter the number of "open" network pathways supplying the recorded neuron with tactile information.…”
Section: Introductionmentioning
confidence: 99%